The Role of Social Media in the Transformation of Contemporary Da'wah: A Literature Review of Its Effectiveness and Challenges - Ahmad Syarif; Salma Nurjannah (Samarinda International Journal of Islamic Studies (SIJIS), 2024)
This literature review examines the multifaceted role of social media in the transformation of contemporary da'wah (Islamic proselytization). It explores the effectiveness of social media platforms in disseminating Islamic teachings, fostering community engagement, and addressing the evolving needs of the modern Muslim community. The review synthesizes existing research to analyze the opportunities and challenges presented by digital da'wah, including its impact on cultural and methodological changes in Islamic communication. The methodology involves a comprehensive analysis of scholarly articles, books, and online resources, focusing on themes such as content strategies, audience reception, and the ethical considerations of online da'wah. Key findings highlight the significant reach and accessibility of social media in spreading Islamic messages, alongside concerns regarding message distortion, content credibility, and the potential for the spread of misinformation. This review identifies strategies for maximizing the positive impact of social media in da'wah while mitigating its risks, offering insights for practitioners, scholars, and policymakers. The study concludes by emphasizing the need for a cautious and responsible approach to ensure that religious messages remain accurate, beneficial, and aligned with the core values of Islam.